Experimental study on hardening characteristics and loading rate dependent mechanical behaviour of gypsum mixed sand. (30th November 2020) - Maqsood, Zain; Koseki, Junichi; Ahsan, Md. Kamrul; Shaikh, Masum; Kyokawa, Hiroyuki
Highlights: Reliability assessment criterion of test results based on local strain measurements. Reduction in peak strength of Gypsum Mixed Sand (GMS) during first month of ageing. No effects of ageing on the mechanical behaviour of GMS after first month. Significant loading rate dependency of GMS, especially at slower loading rates. No interaction between ageing and loading rate effects for GMS. Abstract: Gypsum is among the widely used construction materials, and is nowadays been considered for a variety of applications including soil stabilization, foundation works, grouting and brick manufacturing etc. Considering this prevalent utilization of gypsum in construction industry, a comprehensive study was conducted to examine the time-dependent strength and deformation characteristics of Gypsum Mixed Sand (GMS) by examining the hardening characteristics (up to nine months) and loading rate (up to five folds); under unconfined monotonic loading conditions. Effects of different factors including gypsum content, hemihydrate batches and interaction between ageing and loading rate were considered to rationally comprehend the time-dependent mechanical behaviour of GMS. The results revealed an obvious reduction in the peak strength of GMS during the initial month of ageing, and no further effects of ageing were witnessed afterwards. Moreover, a unique and significant dependency of strength and deformation on the loading rate was observed for GMS, and this behaviour was categorized into three different zones of loading rates.